α-Ketoglutarate promotes autophagic activity under a peri-implant condition to enhance osseointegration of dental implant in rats with osteoporosis - Chen, Luyuan; Li, Qisen; Ma, Shengnan; Wang, Bohua (Connective tissue research, 2025)
We aimed to investigate whether α-ketoglutarate (AKG) can promote autophagic activity under a peri-implant condition to enhance the osseointegration of dental implant in rats with osteoporosis (OP). Con, Model and AKG groups were established for the random allocation of thirty rats ( = 10). Their bone metabolism indicators were measured. The peri-implant bone morphology was detected by toluidine blue staining, the peri-implant bone tissue healing was detected, and the implant torque was measured. In comparison to the Con group, the bone metabolism indicators [bone volume/tissue volume ratio (BV/TV), trabecular number (Tb.N), and osseointegration index (OI)], bone-implant contact (BIC) rate, bone mass in the cancellous area, dislocation torque, protein and mRNA expressions of bone morphogenetic protein-2 (BMP-2), RUNX2 and Beclin1, and LC3II/LC3I ratio in bone tissues decreased significantly in the Model group, with a significant enlargement of trabecular space (Tb.Sp) ( < 0.05). In comparison with the Model group, the AKG group had significant increases in Tb.N, BV/TV, OI, BIC rate, bone mass in the cancellous area, dislocation torque, mRNA plus protein expressions of BMP-2, Runt-related transcription factor 2 and Beclin1, and LC3II/light chain 3I ratio in bone tissues, in addition to a significant reduction of Tb.Sp ( < 0.05). AKG may relieve the bone metabolism disorders and enhance the osteogenic differentiation and osseointegration of implants in OP rats by promoting peri-implant autophagy.